(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: تهدف الدراسة إلى التعرف على الحاجات الإرشادية لذوي صعوبات التعلم بالأقسام المدمجة من وجهة نظر أساتذتهم خلال الموسم الدراسي 2020/2021، تم اختيار عينة مقصودة تتكون من 06 أساتذة بالأقسام المدمجة بولاية مستغانم، وسعيا لتحقيق أهداف الدراسة استخدم الباحثان المقابلة كأداة لجمع المعلومات المتعلقة بموضوعها. وتوصلت نتائج الدراسة إلى أن هناك مستوى مرتفع للحاجات الإرشادية لذوي صعوبات التعلم بالأقسام المدمجة، مع وجود مستوى متوسط للحاجة إلى التدريب على المهارات الأولية للقراءة والكتابة والحساب، وكذا الحاجة إلى التدريب على مهارات التناسق البصري – الحركي، والضبط الحركي. وخلصت الدراسة في الأخير إلى ضرورة التشخيص الجيّد للفئات المستهدفة من الدمج حسب نوع الإعاقة ودرجتها. كلمات دالة:حاجات إرشادية, صعوبات تعلم, مدرسة, دمج, أقسام مدمجة. Abstract: This Study Aimed To Know The Indicative Needs Of Learners With Learning Difficulties In Integrated Sections From The Perspective Of Their Teachers During The 2020/2021 School Season. And Anticipated Sample Of 06 Teachers Was Selected From Integrated Sections In Mostaganem State. And To Achieve The Research Goals, The Researchers Were Used Interview As A Tool To Gather Information On Its Subject. The Results Of The Study Revealed A High Level Of Indicative Learning Disability Needs In The Integrated Sections, With An Average Level Of Training Needs In Reading, Writing And Arithmetic, As Well As The Need For Training In Visual-Motor Alignment Skills And Motor Control. Finally, The Study Concluded That Integration Target Groups Should Be Properly Diagnosed According To Type And Degree Of Disability. Key Words: Indicative Needs, Learning Difficulties, School, Integration, Integrated Sections.